TREATMENT OF ACUTE PROMYELOCYTIC LEUKEMIA WITH HIGH WHITE CELL BLOOD COUNTS. - Charicleia Kelaidi; Lionel Ades; Pierre Fenaux (Mediterranean Journal of Hematology and Infectious Diseases)
Acute promyelocytic leukemia (APL) with WBC above 10 G/L has long been considered, even in the all-trans retinoic acid (ATRA) era, to carry a relatively poor prognosis (compared to  APL with WBC below 10 G/L), due to increased early mortality and relapse. However, early deaths can to a large extent be avoided if specific measures are rapidly instigated, including prompt referral to a specialized center, immediate onset of ATRA and chemotherapy, treatment of coagulopathy with adequate platelet transfusional support, and prevention and management of differentiation syndrome. Strategies to reduce relapse rate include chemotherapy reinforcement with cytarabine and/or arsenic trioxide during consolidation, prolonged maintenance treatment, especially with ATRA and low dose chemotherapy, and possibly, although this is debated, intrathecal prophylaxis to prevent central nervous system relapse. By applying those measures, outcomes of patients with high risk APL have considerably improved, and have become in many studies almost similar to those of standard risk APL patients.